Expected potential hemipteran vectors of Xylella fastidiosa bacterium in olive and vineyard groves of the Egyptian northwestern coast - I. Ahmed Imam; I. Iman El-Sebaey; Abdel Nasser A. Kobisi; Manar A. Elagory; Amany N. Mansour (Heliyon, 2024)
Xylella fastidiosa was recently added to the list of threatening pathogens affecting more than 300 plant hosts. Hemipteran hoppers that feed on xylem have been documented as potential transmitters. Hemipteran hoppers, known vectors for plant pathogens via xylem feeding, pose significant risks to agriculture. Despite their role in transmitting diseases, comprehensive data on their species diversity, distribution, and seasonal patterns, particularly in critical agricultural zones, remain sparse. Hence, the current study was carried out at 14 sites (eight olive farms and six vineyards) during the 2021/2022 season to develop a comprehensive checklist of hopper species present on the Egyptian Northwestern Coast, including their seasonal and location distribution, to serve as a real roadmap supporting control strategies if the pathogen breaches Egyptian borders. Utilizing 560 yellow sticky traps, we collected data seasonally, resulting in the identification of 21 hopper species belonging to 14 genera within four families. Olive orchards harbored a higher number of hoppers compared to vineyards, with Empoasca decipiens being the most dominant species. Our findings provide a foundational checklist and highlight the importance of continued monitoring and detailed studies to support proactive control strategies against potential X. fastidiosa outbreaks. We used 560 yellow sticky traps at 10 traps per site (80 traps for olive orchards and 60 traps for the vineyard per season) throughout the study period. Traps were installed at two levels to catch hopper species harboring tree canopies and ground vegetation. Each trap was replaced every 7 days, and the collected trap sheets were sent to the laboratory for segregation and identification. The data revealed 21 hopper species belonging to 14 genera and 4 families, with cicadellid species being the most represented (14 species). Olive orchards harbored a higher number of hoppers than vineyards. Empoasca decipiens exhibited the highest dominance among the remaining species. Although summer sampling yielded the highest number of hopper species and trapped specimens, seasonal variation in the distribution pattern exhibited non-significant differences (F = 1.7 and P = 0.173). Ras El-Hekma had the highest species representation (21 species), whereas El-Negala had the highest species richness. The lowest species representation at the Barrani location had the highest abundance of caught specimens. Although there were fluctuations in the trapped specimens among the examined locations, statistical analysis revealed no significant differences (F = 0.67, P = 0.58). Cluster analysis revealed distinct groupings with different degrees of similarity for both seasonal and location distributions. The impact of trap height on the hopper capture pattern showed a biased tendency towards low traps. Diversity indices showed no significant differences between the examined locations. Although our results offer a foundation for potential control strategies against X. fastidiosa, further detailed studies are required to fill the knowledge gap regarding its suspected vectors. Such research will guide management strategies that can be applied in cases where this infectious bacterium crosses Egyptian borders.